Sonolysis of Escherichia coli and Pichia pastoris in microfluidics - Tandiono, Tandiono (2013)
We report on an efficient ultrasound based technique for lysing Escherichia coli and Pichia pastoris with oscillating cavitation bubbles in an integrated microfluidic system. The system consists of a meandering microfluidic channel and four piezoelectric transducers mounted on a glass substrate, with the ultrasound exposure and gas pressure regulated by an automatic control system. Controlled lysis of bacterial and yeast cells expressing green fluorescence protein (GFP) is studied with high-speed photography and fluorescence microscopy, and quantified with real-time polymerase chain reaction (qRT-PCR) and fluorescence intensity. The effectiveness of cell lysis correlates with the duration of ultrasound exposure. Complete lysis can be achieved within one second of ultrasound exposure with a temperature increase of less than 3.3 °C. The rod-shaped E. coli bacteria are disrupted into small fragments in less than 0.4 seconds, while the more robust elliptical P. pastoris yeast cells require around 1.0 second for complete lysis. Fluorescence intensity measurements and qRT-PCR analysis show that functionality of GFP and genomic DNA for downstream analytical assays is maintained.